The Relationship between Personal Hygiene, Maternal Health Status, and History of Diarrhea to Stunting Cases in Indonesia: Systematic Review - Serly Santiyah Serly Santiyah; Rahmatillah Razak; Anggun Budiastuti; Elvi Sunarsih; Ranti Ekasari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: The government established a goal of a prevalence rate of 14% by the end of 2024 because the number of stunting cases in Indonesia is still high, at 21.6%. This review aims to provide the factors such as personal hygiene, maternal health status, and diarrhea that cause stunting and recommendations for more effective health policies to prevent stunting in Indonesia. The purpose of this study is to examine the connection between personal hygiene, maternal health status, and a history of diarrhea with the occurrence of stunting in Indonesia.. Method: This study uses a systematic review method on observational studies with a case control and cross-sectional research design conducted in Indonesia published between 2019 and 2024. Databases such as PubMed, ScienceDirect, and Google Scholar are used to search for eligible articles. The quality of the publication was then assessed using The JBI (Joanna Briggs Institute) Critical Appraisal Tools. Result: A total of 210 articles were taken from the database, and 17 research articles were included in this study. In the article studied, the factors that are most often associated with stunting are personal hygiene practices (behavior of washing hands with soap), maternal weight, maternal height, and infectious diseases such as diarrhea related to stunting. Conclusion: A study of 17 articles showed that personal hygiene, maternal health status during pregnancy, and history of diarrhea contributed significantly to the incidence of stunting in Indonesia. Poor personal hygiene and diarrheal infections can worsen children's nutritional status, increase the risk of infection, and inhibit optimal growth and development. These factors are an important component in efforts to prevent stunting through improving hygiene, maternal health, and infection management.